The Strengthening of Local Wisdom, Hinduism, and the Ideology of Pancasila in Bali - I Ketut Ardhana (Andalas International Journal of Socio-Humanities, 2022)
Recently, significant issues have emerged related to the existence of local wisdom synergize with the presence of religion in strengthening the ideology of the Indonesian state based on Pancasila. This is inseparable from the contestation between local culture and outside culture which is expected not to be disturbing because it is deeply rooted in Bali in particular and in the archipelago in general. Bali is taken as an object of study with the consideration of the existence of local wisdom that is quite strong and able to synergize with the dynamics of Hinduism and seems to be able to strengthen the ideological values of Pancasila. Related to this issue in this paper discussed how local culture in this regard the values of local wisdom that already exist can be proven to strengthen the existence of religions that come later which seem to strengthen the ideological values of Pancasila. For more details, the following will be cultivated. First, what is considered a local culture or wisdom that existed before the entry of major religions in the region, second: how the formation of local wisdom values that can accept the influence of these major religions, and thirdly how can it be interpreted that there is a synergistic relationship between local wisdom, religious influence and strengthening of Pancasila values in the context of nation-state building in Indonesia in general.